Soluções esfericamente simétricas e inflação em teorias de gravidade de ordens superiores - Silva Neto, Gesiel Rodrigues da (2022)
Extensions of general relativity in which higher-order curvature corrections are included in Einstein-Hilbert’s action have received increasing attention mainly by model building in high-energy physics — string theory and quantum gravity — and in the accelerated expansion of the very early universe. In this PhD thesis, we proposed a higher-order gravity, characterized by the inclusion of all correction terms up to the second-order involving the Ricci scalar. From then on, we approached two topics of interest. The first topic concerns the investigation of spherically symmetric solutions, where we explored weak-field regime and black hole solutions. We obtained all solutions in the weak-field regime and also addressed the issue of the possibility of existence of non-Schwarzschild black hole solutions. In turn, the second topic involves research in the context of cosmic inflation, motivated by the success of the Starobinsky model. In this sense, we developed a detailed research of Starobinsky+R3 and Starobinsky+R3 + RR inflationary models, confronting them with the most recent observational data from the Planck satellite and the BICEP3/Keck Array.